Coal gangue concrete, building component and method for improving freeze-thaw durability of the component
Patent Information
- Application Number
- CN202611100862.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-20
AI Technical Summary
另一方面,针对此类孔隙结构不良的基体,单一的硅酸钠溶液处理效果有限
[0015]本发明提供的煤矸石混凝土、建筑构件及提升构件抗冻融耐久性的方法的有益效果包括:
Smart Images

Figure REF-OBJ-1784793607752-000002 
Figure REF-OBJ-1784793607752-000003 
Figure REF-OBJ-1784793607752-000004
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a method for improving the freeze-thaw resistance and durability of coal gangue concrete, building components, and lifting components. Background Technology
[0002] Coal gangue is a solid waste generated during coal mining and washing. Crushing it and using it as aggregate to prepare concrete is an important way to dispose of large quantities of solid waste and reduce the mining of natural sand and gravel. Existing research on coal gangue mainly focuses on improving the mechanical strength of concrete by adjusting the coal gangue aggregate replacement rate and optimizing the mix proportion. However, in practical applications, especially in areas with frequent freeze-thaw cycles, the main bottleneck faced by coal gangue concrete is insufficient durability. To address this, some studies have attempted to use surface coating technology for protection, such as coating with a reaction-hardening sodium silicate solution. This allows the coating to react with cement hydration products to form hydrated calcium silicate gel, thereby blocking pore channels, preventing external moisture intrusion, and thus improving the freeze-thaw resistance of the concrete.
[0003] However, extensive engineering practice and my own comparative experiments show that existing technologies for coal gangue concrete and their surface treatment methods have significant shortcomings. On the one hand, coal gangue aggregates, especially manufactured sand, have well-developed microcracks and high water absorption, resulting in poor workability and high water demand in the concrete mixture. After hardening, the internal porosity increases, forming interconnected capillary channels that provide pathways for water intrusion. Under freeze-thaw cycles, the expansion of external moisture during freezing generates repeated stress, gradually loosening and cracking the internal structure of the concrete, ultimately leading to surface peeling, flaking, and a sharp decline in strength. On the other hand, for such poorly structured matrices, the effect of a single sodium silicate solution is limited. The hydrated calcium silicate gel generated by the reaction is insufficient to completely seal the numerous honeycomb-like pores and microcracks present in coal gangue concrete, causing the coating to "fail" and failing to effectively block moisture. Therefore, under freeze-thaw cycles, the deterioration process of coal gangue concrete remains very rapid, and existing single-coating protection measures are insufficient to meet the needs of practical engineering projects. Summary of the Invention
[0004] This invention provides a method for improving the freeze-thaw resistance and durability of coal gangue concrete, building components, and lifting components, in order to solve the problems mentioned in the background art.
[0005] This invention provides a coal gangue concrete, comprising the following raw materials in parts by weight: 4-7 parts ordinary silicate cement, 10-13 parts natural fine aggregate, 5-7 parts coal gangue coarse aggregate, 9-11 parts natural coarse aggregate, 0.04-0.07 parts silane coupling hydrophobic agent, 2-3.5 parts water, and 0.09-0.12 parts polycarboxylate high-performance water-reducing agent.
[0006] Optionally, the coal gangue coarse aggregate is nano-SiO2-reinforced coal gangue coarse aggregate, and its preparation process is as follows: (1) Screen the coarse aggregate of coal gangue with a particle size of 5-20 mm and wash it; (2) After cleaning, put the coarse aggregate of coal gangue into an oven to dry, take it out and cool it to room temperature for later use; (3) Select nano-SiO2 with an average particle size of 15±5nm and prepare it into a solution with a concentration range of 2.7%-3.2%; (4) The dried coal gangue coarse aggregate is completely immersed in the nano silica aqueous solution obtained in step (3) and soaked at 20±2℃ for 24h, stirring once every 6h during the soaking period; (5) After soaking, take out the coarse aggregate of coal gangue, drain the surface moisture and put it into a 60℃ forced-air drying oven to dry to constant weight; (6) After drying, cool to room temperature to obtain the product.
[0007] Optionally, the preparation process of the silane coupling hydrophobic agent is as follows: (1) Weigh the following raw materials according to the following weight proportions: 100 parts mica powder, 5 parts silane coupling agent KH550, and 3 parts polydimethylsiloxane; (2) Add deionized water to the dried mica at a mass ratio of 1:5 and ultrasonically disperse for 30 min; (3) Mix the silane coupling agent KH550 with the ethanol solution at a mass ratio of 1:20 and stir and hydrolyze in a 60℃ water bath for 30 min. The mass ratio of anhydrous ethanol to deionized water in the ethanol solution is 95:5. Adjust the pH to 4-5 with acetic acid before use. (4) Under stirring conditions, slowly add the hydrolysate obtained in step (3) to the mica slurry obtained in step (2) and mix evenly; (5) Continue stirring the material, add polydimethylsiloxane, stir for 2 hours in a 60°C water bath, filter, and wash the filter cake with anhydrous ethanol. (6) After washing, dry the filter cake to constant weight, grind it and pass it through a 200-mesh sieve to obtain the final product.
[0008] Optionally, the strength grade of the ordinary Portland cement is 42.5, and the ratio of water to ordinary Portland cement is 0.5; the amount of silane coupling hydrophobic agent is 1% of the amount of ordinary Portland cement.
[0009] Optionally, the natural coarse aggregate is crushed stone with a continuous gradation of 5-31.5 mm in size, wherein the ratio of 5-10 mm: 10-20 mm: 16-31.5 mm is 2:5:3; the natural fine aggregate is medium sand from river sand with a fineness modulus of 2.6.
[0010] Optionally, the preparation method of coal gangue concrete includes the following steps: (1) 4-7 parts of ordinary silicate cement, 10-13 parts of natural fine aggregate, 5-7 parts of coal gangue coarse aggregate, 9-11 parts of natural coarse aggregate, 0.04-0.07 parts of silane coupling hydrophobic agent, 2-3.5 parts of water, and 0.09-0.12 parts of polycarboxylate high-performance water-reducing agent; (2) The weighed coal gangue coarse aggregate is pre-wetted until it reaches a saturated surface dry state, then drained of surface moisture and set aside for later use. (3) Add ordinary silicate cement, natural fine aggregate, silane coupling hydrophobic agent, coal gangue coarse aggregate and natural coarse aggregate into a mixer and mix evenly. Then add 70% water and continue mixing evenly. Then add polycarboxylate high-performance water-reducing agent and the remaining water and continue mixing evenly. (4) Pour the mixed slurry into the mold and compact it on the vibrating table. After compaction for 24 hours, remove the mold and cure it in a curing room with a temperature of 20±2℃ and a humidity of ≥95% for 28 days. After curing, coal gangue concrete is obtained.
[0011] The present invention also provides a coal gangue concrete component, which is made of the above-mentioned concrete material.
[0012] The present invention also provides a method for improving the freeze-thaw resistance of the above-mentioned concrete components, comprising the following steps: (1) Clean the surface of the component and then let it air dry naturally; (2) Apply the composite emulsion evenly to all exposed surfaces, with a coating amount of 0.25-0.3 kg / m². 2 After the first coat is applied, let it stand in a dry environment for 8 hours to allow it to dry to the touch. Then apply the second coat, using the same amount as the first coat. After the second coat is dry to the touch, immerse the component in the composite emulsion for about 10 seconds, remove it, drain off the excess liquid, and cure it in a dry environment for 72 hours to allow it to fully harden.
[0013] Optionally, the preparation process of the composite emulsion is as follows: (1) Weigh 2 parts of modified nano-SiO2, add 15 parts of deionized water, and ultrasonically disperse for 15 min to prepare a pre-dispersed slurry; (2) Under stirring conditions, the pre-dispersed slurry is slowly added to 100 parts of styrene-acrylic emulsion; (3) Then add 1 part dodecyl alcohol ester, 0.5 part AMP-95 and 0.3 part defoamer to the system in sequence, and stir at 1000 rpm for 15 min to make the components evenly dispersed; (4) Adjust the viscosity of the emulsion to 20-25s using deionized water and let it stand to defoam.
[0014] Optionally, the preparation process of modified nano-SiO2 is as follows: (1) Weigh 1 part of nano SiO2 with an average particle size of 30±5nm, add 10 parts of anhydrous ethanol and 5 parts of deionized water, disperse ultrasonically for 30min, and then adjust the pH to 4-5 with dilute hydrochloric acid. (2) Add 0.5 parts of KH560 to the system and continue ultrasonic dispersion for 10 min; (3) Stir the system containing KH560 in a 70°C water bath for 3 hours; (4) After the reaction is complete, centrifuge the product and wash the precipitate; (5) Dry the precipitate under vacuum to constant weight, then grind it.
[0015] The beneficial effects of the method for improving the freeze-thaw resistance of coal gangue concrete, building components, and lifting components provided by this invention include: 1. By using a specific proportion of coal gangue coarse aggregate to replace part of the natural coarse aggregate in the preparation of concrete, the problem of deterioration of the workability of the mixture caused by the use of coal gangue fine aggregate is avoided, and the mechanical properties and long-term durability of coal gangue concrete are improved.
[0016] 2. By immersing and strengthening coarse coal gangue aggregate in a nano-silica suspension, the nanoparticles pre-fill the pores on the surface of the aggregate, which seals the surface defects of the aggregate, strengthens the interface between the aggregate and the paste, reduces the water absorption rate of coal gangue, and improves the compressive strength and overall compactness of concrete.
[0017] 3. By incorporating a powdered hydrophobic agent with mica powder as the matrix and synergistic modification by silane coupling agent and polydimethylsiloxane during the concrete mixing process, a hydrophobic film layer is formed on the inner wall of the capillary, blocking the transmission of moisture, thereby achieving the effect of reducing the water absorption rate from the inside of the concrete matrix and delaying the penetration of moisture and corrosive media.
[0018] 4. By coating the surface of concrete components with a high-density coating composed of modified nano-silica and styrene-acrylic emulsion, the coating fully fills the micropores and microcracks on the concrete surface, thereby preventing the entry of external liquid water, improving the component's resistance to freeze-thaw cycles, and extending its service life. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1This is a surface damage morphology diagram of a concrete building component provided in Embodiment 1 of the present invention; Figure 2 This is a surface damage morphology diagram of a concrete building component provided in Embodiment 2 of the present invention; Figure 3 This is a surface damage morphology diagram of a concrete building component provided in Embodiment 3 of the present invention; Figure 4 This is a surface damage morphology diagram of a concrete building component provided in Embodiment 4 of the present invention; Figure 5 This is a surface damage morphology diagram of a concrete building component provided in Embodiment 5 of the present invention; Figure 6 This is a surface damage morphology diagram of a concrete building component provided in Comparative Example 1 of the present invention; Figure 7 This is a surface damage morphology diagram of a concrete building component provided in Comparative Example 2 of the present invention; Figure 8 This is a surface damage morphology diagram of a concrete building component provided in Comparative Example 3 of the present invention; Figure 9 This is a surface damage morphology diagram of a concrete building component provided in Comparative Example 4 of the present invention; Figure 10 This is a surface damage morphology diagram of a concrete building component provided in Comparative Example 5 of the present invention; Figure 11 This is a diagram showing the surface damage morphology of a concrete building component provided in Comparative Example 6 of the present invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are also within the scope of protection of the present invention.
[0022] This invention provides a coal gangue concrete, comprising the following raw materials in parts by weight: 4-7 parts ordinary silicate cement, 10-13 parts natural fine aggregate, 5-7 parts coal gangue coarse aggregate, 9-11 parts natural coarse aggregate, 0.04-0.07 parts silane coupling hydrophobic agent, 2-3.5 parts water, and 0.09-0.12 parts polycarboxylate high-performance water-reducing agent.
[0023] The raw materials for the coal gangue concrete provided by this invention include ordinary Portland cement, natural fine aggregate, coal gangue coarse aggregate, natural coarse aggregate, silane coupling hydrophobic agent, polycarboxylate high-performance water-reducing agent, and water. Ordinary Portland cement serves as the cementitious material, providing sufficient strength for the concrete. Natural fine aggregate primarily acts as a filler, reducing the pore volume within the concrete and increasing its density; it also forms the mortar matrix together with the cement paste, encapsulating the coarse aggregate particles and giving the mixture good fluidity and workability. Coal gangue is a solid waste generated during coal mining and washing. Crushing and processing it to replace part of the natural coarse aggregate in concrete production not only disposes of industrial solid waste and reduces the mining of natural stone but also lowers the raw material costs of concrete. Controlling the amount of coal gangue coarse aggregate to 5-7 parts, forming a reasonable substitution ratio with 9-11 parts of natural coarse aggregate, ensures sufficient solid waste disposal while avoiding excessive damage to the density and frost resistance of the concrete due to excessive coal gangue content. Natural coarse aggregate forms the main skeleton of concrete, providing a stable volumetric framework and high compressive strength. Silane coupling hydrophobic agents are uniformly dispersed within the concrete paste during mixing. Their surface contains hydrophobic groups, which form a hydrophobic film on the capillary walls and interfacial transition zones of the hardened cement paste. This reduces the ability of liquid water to penetrate and migrate into the concrete, decreasing the total amount and migration rate of freezeable water during freeze-thaw cycles. Polycarboxylate superplasticizers can significantly reduce water consumption while maintaining concrete fluidity, thereby lowering the water-cement ratio, reducing capillary porosity within the concrete, and improving its density and durability.
[0024] Preferably, the coal gangue concrete comprises the following raw materials in parts by weight: 5.5 parts ordinary silicate cement, 11.5 parts natural fine aggregate, 5.8 parts coal gangue coarse aggregate, 10.2 parts natural coarse aggregate, 0.06 parts silane coupling hydrophobic agent, 2.8 parts water, and 0.1 parts polycarboxylate high-performance water-reducing agent.
[0025] Furthermore, the coal gangue coarse aggregate is nano-SiO2-reinforced coal gangue coarse aggregate, and its preparation process is as follows: (1) Screen the coarse aggregate of coal gangue with a particle size of 5-20 mm and wash it; (2) After cleaning, put the coarse aggregate of coal gangue into an oven to dry, take it out and cool it to room temperature for later use; (3) Select nano-SiO2 with an average particle size of 15±5nm and prepare it into a solution with a concentration range of 2.7%-3.2%; (4) The dried coal gangue coarse aggregate is completely immersed in the nano silica aqueous solution obtained in step (3) and soaked at 20±2℃ for 24h, stirring once every 6h during the soaking period; (5) After soaking, take out the coarse aggregate of coal gangue, drain the surface moisture and put it into a 60℃ forced-air drying oven to dry to constant weight; (6) After drying, cool to room temperature to obtain the product.
[0026] Coal gangue coarse aggregate was immersed in a silica dispersion, allowing nano-SiO2 particles to penetrate into the microcracks and open pores on the surface of the coal gangue aggregate. After immersion, the aggregate was dried to constant weight. During this process, nano-SiO2 particles deposited on the inner walls of the pores on the aggregate surface. On the one hand, this filled the pores and microcracks on the aggregate surface, sealing surface defects and reducing the water absorption rate of the coal gangue. On the other hand, nano-SiO2 has high pozzolanic activity and can react with calcium hydroxide produced during cement hydration to generate additional CSH gel, strengthening the interfacial transition zone between the aggregate and the cement paste and improving interfacial bond strength.
[0027] Furthermore, the preparation process of the silane coupling hydrophobic agent is as follows: (1) Weigh the following raw materials according to the following weight proportions: 100 parts mica powder, 5 parts silane coupling agent KH550, and 3 parts polydimethylsiloxane; (2) Add deionized water to the dried mica at a mass ratio of 1:5 and ultrasonically disperse for 30 min; (3) Mix the silane coupling agent KH550 with the ethanol solution at a mass ratio of 1:20 and stir and hydrolyze in a 60℃ water bath for 30 min. The mass ratio of anhydrous ethanol to deionized water in the ethanol solution is 95:5. Adjust the pH to 4-5 with acetic acid before use. (4) Under stirring conditions, slowly add the hydrolysate obtained in step (3) to the mica slurry obtained in step (2) and mix evenly; (5) Continue stirring the material, add polydimethylsiloxane, stir for 2 hours in a 60°C water bath, filter, and wash the filter cake with anhydrous ethanol. (6) After washing, dry the filter cake to constant weight, grind it and pass it through a 200-mesh sieve to obtain the final product.
[0028] Furthermore, the strength grade of the ordinary Portland cement is 42.5, and the ratio of water to ordinary Portland cement is 0.5; the amount of silane coupling hydrophobic agent is 1% of the amount of ordinary Portland cement.
[0029] Furthermore, the natural coarse aggregate is crushed stone with a continuous gradation of 5-31.5mm in size, wherein the ratio of 5-10mm:10-20mm:16-31.5mm is 2:5:3; the natural fine aggregate is medium sand from river sand with a fineness modulus of 2.6.
[0030] Furthermore, the preparation method of coal gangue concrete includes the following steps: (1) 4-7 parts of ordinary silicate cement, 10-13 parts of natural fine aggregate, 5-7 parts of coal gangue coarse aggregate, 9-11 parts of natural coarse aggregate, 0.04-0.07 parts of silane coupling hydrophobic agent, 2-3.5 parts of water, and 0.09-0.12 parts of polycarboxylate high-performance water-reducing agent; (2) The weighed coal gangue coarse aggregate is pre-wetted until it reaches a saturated surface dry state, then drained of surface moisture and set aside for later use. (3) Add ordinary silicate cement, natural fine aggregate, silane coupling hydrophobic agent, coal gangue coarse aggregate and natural coarse aggregate into a mixer and mix evenly. Then add 70% water and continue mixing evenly. Then add polycarboxylate high-performance water-reducing agent and the remaining water and continue mixing evenly. (4) Pour the mixed slurry into the mold and compact it on the vibrating table. After compaction for 24 hours, remove the mold and cure it in a curing room with a temperature of 20±2℃ and a humidity of ≥95% for 28 days. After curing, coal gangue concrete is obtained.
[0031] The present invention also provides a coal gangue concrete component, which is made of the above-mentioned concrete material.
[0032] The present invention also provides a method for improving the freeze-thaw resistance of the above-mentioned concrete components, comprising the following steps: (1) Clean the surface of the component and then let it air dry naturally; (2) Apply the composite emulsion evenly to all exposed surfaces, with a coating amount of 0.25-0.3 kg / m². 2 After the first coat is applied, let it stand in a dry environment for 8 hours to allow it to dry to the touch. Then apply the second coat, using the same amount as the first coat. After the second coat is dry to the touch, immerse the component in the composite emulsion for about 10 seconds, remove it, drain off the excess liquid, and cure it in a dry environment for 72 hours to allow it to fully harden.
[0033] Furthermore, the preparation process of the composite emulsion is as follows: (1) Weigh 2 parts of modified nano-SiO2, add 15 parts of deionized water, and ultrasonically disperse for 15 min to prepare a pre-dispersed slurry; (2) Under stirring conditions, the pre-dispersed slurry is slowly added to 100 parts of styrene-acrylic emulsion; (3) Then add 1 part dodecyl alcohol ester, 0.5 part AMP-95 and 0.3 part defoamer to the system in sequence, and stir at 1000 rpm for 15 min to make the components evenly dispersed; (4) Adjust the viscosity of the emulsion to 20-25s using deionized water and let it stand to defoam.
[0034] Furthermore, the preparation process of modified nano-SiO2 is as follows: (1) Weigh 1 part of nano SiO2 with an average particle size of 30±5nm, add 10 parts of anhydrous ethanol and 5 parts of deionized water, disperse ultrasonically for 30min, and then adjust the pH to 4-5 with dilute hydrochloric acid. (2) Add 0.5 parts of KH560 to the system and continue ultrasonic dispersion for 10 min; (3) Stir the system containing KH560 in a 70°C water bath for 3 hours; (4) After the reaction is complete, centrifuge the product and wash the precipitate; (5) Dry the precipitate under vacuum to constant weight, then grind it.
[0035] The present invention will be further described in detail below with reference to specific embodiments.
[0036] Preparation Example 1 Preparation of coarse aggregate from coal gangue: (1) Screen the coarse aggregate of coal gangue with a particle size of 5-20 mm and wash it; (2) After cleaning, put the coarse aggregate of coal gangue into an oven to dry, take it out and cool it to room temperature for later use; (3) Select nano-SiO2 with an average particle size of 15±5nm and prepare it into a solution with a concentration range of 3%; (4) The dried coal gangue coarse aggregate is completely immersed in the nano silica aqueous solution obtained in step (3) and soaked at 20±2℃ for 24h, stirring once every 6h during the soaking period; (5) After soaking, take out the coarse aggregate of coal gangue, drain the surface moisture and put it into a 60℃ forced-air drying oven to dry to constant weight; (6) After drying, cool to room temperature to obtain the product.
[0037] Preparation Example 2 Preparation of silane coupling hydrophobic agents: (1) Weigh the following raw materials according to the following weight proportions: 100 parts mica powder, 5 parts silane coupling agent KH550, and 3 parts polydimethylsiloxane; (2) Add deionized water to the dried mica at a mass ratio of 1:5 and ultrasonically disperse for 30 min; (3) Mix the silane coupling agent KH550 with the ethanol solution at a mass ratio of 1:20 and stir and hydrolyze in a 60℃ water bath for 30 min. The mass ratio of anhydrous ethanol to deionized water in the ethanol solution is 95:5. Adjust the pH to 4-5 with acetic acid before use. (4) Under stirring conditions, slowly add the hydrolysate obtained in step (3) to the mica slurry obtained in step (2) and mix evenly; (5) Continue stirring the material, add polydimethylsiloxane, stir for 2 hours in a 60°C water bath, filter, and wash the filter cake with anhydrous ethanol. (6) After washing, dry the filter cake to constant weight, grind it and pass it through a 200-mesh sieve to obtain the final product.
[0038] Preparation Example 3 Preparation of modified nano-SiO2: (1) Weigh 1 part of nano SiO2 with an average particle size of 30±5nm, add 10 parts of anhydrous ethanol and 5 parts of deionized water, disperse ultrasonically for 30min, and then adjust the pH to 4-5 with dilute hydrochloric acid. (2) Add 0.5 parts of KH560 to the system and continue ultrasonic dispersion for 10 min; (3) Stir the system containing KH560 in a 70°C water bath for 3 hours; (4) After the reaction is complete, centrifuge the product and wash the precipitate; (5) Dry the precipitate under vacuum to constant weight, then grind it.
[0039] Preparation Example 4 Preparation of composite emulsions: (1) Weigh 2 parts of the modified nano-SiO2 obtained in Preparation Example 3, add 15 parts of deionized water, and ultrasonically disperse for 15 min to prepare a pre-dispersed slurry; (2) Under stirring conditions, the pre-dispersed slurry is slowly added to 100 parts of styrene-acrylic emulsion; (3) Then add 1 part dodecyl alcohol ester, 0.5 part AMP-95 and 0.3 part defoamer to the system in sequence, and stir at 1000 rpm for 15 min to make the components evenly dispersed; (4) Adjust the viscosity of the emulsion to 20-25s using deionized water and let it stand to defoam.
[0040] Example 1
[0041] A coal gangue concrete comprises the following raw materials in parts by weight: 5.5 parts of ordinary Portland cement with a strength grade of 42.5, 11.5 parts of natural fine aggregate, 5.8 parts of coal gangue coarse aggregate, 10.2 parts of natural coarse aggregate, 0.06 parts of silane coupling hydrophobic agent, 2.8 parts of water, and 0.1 parts of polycarboxylate high-performance water-reducing agent.
[0042] The coarse aggregate of coal gangue and the silane coupling hydrophobic agent were taken from the raw materials obtained in Preparation Examples 1 and 2, respectively.
[0043] The natural coarse aggregate is crushed stone with a continuous gradation of 5-31.5mm particle size, in which the ratio of 5-10mm:10-20mm:16-31.5mm is 2:5:3.
[0044] The natural fine aggregate is medium sand from river sand, with a fineness modulus of 2.6.
[0045] A coal gangue concrete building component is prepared by the following method: (1) Weigh the raw materials according to the above requirements; (2) The weighed coal gangue coarse aggregate is pre-wetted until it reaches a saturated surface dry state, then drained of surface moisture and set aside for later use. (3) Add ordinary silicate cement, natural fine aggregate, silane coupling hydrophobic agent, coal gangue coarse aggregate and natural coarse aggregate into a mixer and mix evenly. Then add 70% water and continue mixing evenly. Then add polycarboxylate high-performance water-reducing agent and the remaining water and continue mixing evenly. (4) Pour the mixed slurry into a 100mm×100mm×100mm cube mold and compact it on a vibrating table. After compaction for 24 hours, remove the mold and cure it in a curing room with a temperature of 20±2℃ and a humidity of ≥95% for 28 days. After curing, the coal gangue concrete building component is obtained.
[0046] A method for improving the freeze-thaw resistance of building components includes the following steps: (1) Clean the surface of the component and then let it air dry naturally; (2) Take the composite emulsion obtained in Preparation Example 4 and apply it evenly to all exposed surfaces. The application amount is 0.25-0.3 kg / m². 2 After the first coat is applied, let it stand in a dry environment for 8 hours to allow it to dry to the touch. Then apply the second coat, using the same amount as the first coat. After the second coat is dry to the touch, immerse the component in the composite emulsion for about 10 seconds, remove it, drain off the excess liquid, and cure it in a dry environment for 72 hours to allow it to fully harden.
[0047] Example 2
[0048] The difference between Example 2 and Example 1 is that the coal gangue concrete includes the following raw materials in parts by weight: 4 parts of ordinary Portland cement with a strength grade of 42.5, 10 parts of natural fine aggregate, 5 parts of coal gangue coarse aggregate, 9 parts of natural coarse aggregate, 0.04 parts of silane coupling hydrophobic agent, 2 parts of water, and 0.09 parts of polycarboxylate high-performance water-reducing agent.
[0049] Example 3
[0050] The difference between Example 3 and Example 1 is that the coal gangue concrete includes the following raw materials in parts by weight: 7 parts of ordinary Portland cement with a strength grade of 42.5, 13 parts of natural fine aggregate, 7 parts of coal gangue coarse aggregate, 11 parts of natural coarse aggregate, 0.07 parts of silane coupling hydrophobic agent, 3.5 parts of water, and 0.12 parts of polycarboxylate high-performance water-reducing agent.
[0051] Example 4
[0052] The difference between Example 4 and Example 1 is that the coal gangue concrete includes the following raw materials in parts by weight: 5 parts of ordinary Portland cement with a strength grade of 42.5, 11 parts of natural fine aggregate, 5.5 parts of coal gangue coarse aggregate, 10.5 parts of natural coarse aggregate, 0.05 parts of silane coupling hydrophobic agent, 2.5 parts of water, and 0.1 parts of polycarboxylate high-performance water-reducing agent.
[0053] Example 5
[0054] The difference between Example 5 and Example 1 is that the coal gangue concrete includes the following raw materials in parts by weight: 6 parts of ordinary Portland cement with a strength grade of 42.5, 12 parts of natural fine aggregate, 6 parts of coal gangue coarse aggregate, 10 parts of natural coarse aggregate, 0.06 parts of silane coupling hydrophobic agent, 3 parts of water, and 0.11 parts of polycarboxylate high-performance water-reducing agent.
[0055] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the obtained concrete component was not coated with the composite emulsion.
[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the self-made composite emulsion was replaced with a reaction-curing sodium silicate solution (commercially available) during the coating process.
[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the self-made composite emulsion was replaced with a gel-type styrene-acrylic emulsion (commercially available) during the coating process.
[0058] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that no silane coupling hydrophobic agent was used in the coal gangue concrete.
[0059] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the coarse aggregate of coal gangue was not subjected to strengthening treatment.
[0060] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 includes the following raw materials in parts by weight: 5.5 parts of ordinary Portland cement with a strength grade of 42.5, 11.5 parts of natural fine aggregate, 3 parts of coal gangue coarse aggregate, 3 parts of coal gangue fine aggregate, 10.2 parts of natural coarse aggregate, 0.06 parts of silane coupling hydrophobic agent, 2.8 parts of water, and 0.1 parts of polycarboxylate high-performance water-reducing agent. The strengthening method for the coal gangue fine aggregate is the same as that for the coal gangue coarse aggregate.
[0061] The surface damage morphology diagrams of the concrete building components obtained in Examples 1-5 and Comparative Examples 1-6 are shown below. Figure 1-11It should be noted that the numbers written on the components in the photographs in the accompanying drawings are the numbers used by the inventors during the experiment, and do not correspond to the numbers in Tables 1 and 2 later in this application. For the specific correspondence between the accompanying drawings and the embodiments and comparative examples, please refer to the accompanying drawings description of this application.
[0062] The coal gangue concrete building components obtained in Examples 1-5 and Comparative Examples 1-6 were subjected to freeze-thaw cycle tests using the slow freezing method. The steps are as follows: (1) Prepare building components (hereinafter referred to as test pieces), weigh the components in a dry state and record the mass.
[0063] (2) Soak the specimen in water for 24 hours to ensure it is fully saturated with water. Then remove it, wipe off the surface moisture with a damp cloth, and place it in a freezer. The freezer temperature should be maintained between -20℃ and 18℃. Freezing can begin at 10:00 AM and end at 2:30 PM each day. Place the specimen in a thawing container and immediately add water at 18℃-20℃, ensuring the water level is 2cm above the specimen surface. Each freezing cycle should last at least 4 hours, followed by at least 4 hours of thawing, constituting one freeze-thaw cycle. The specimen can be soaked until the next day before being removed for visual inspection. Observe the surface damage, cracks, edge defects, peeling, etc., and record the findings in detail.
[0064] (3) The test blocks that have been soaked until the next day are wiped dry with a damp cloth and then subjected to the next freeze-thaw cycle under saturated water conditions.
[0065] It should be noted that multiple specimens were prepared in each embodiment and comparative example, and the multiple specimens were tested simultaneously. During the test, if a specimen showed severe damage or cracks, the freeze-thaw cycle test of that group of specimens could be stopped.
[0066] During the test, the mass of the specimen in the dry state before and after the freeze-thaw cycle was recorded, and the compressive strength of the component in the dry state before and after the freeze-thaw cycle was also recorded.
[0067] The freeze-thaw cycle test was conducted according to Section 4.1 of GB / T50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Concrete" - Slow Freezing Method.
[0068] The test results of the components obtained in Examples 1-5 are shown in Table 1: Table 1
[0069] The test results of the components obtained in Comparative Examples 1-6 are shown in Table 2: Table 2
[0070] The data above shows that, compared to Example 1, Comparative Example 1 had similar pre-freeze-thaw strength, but its post-freeze-thaw strength was only about 28 MPa, with a strength loss rate as high as 42.9%-46.0%, and the number of surface damage cycles was only 59-64. This indicates that without the protection of a surface coating, coal gangue concrete deteriorates rapidly in a freeze-thaw environment. Comparative Example 2 used a commercially available reaction-hardening sodium silicate solution instead of the composite emulsion, and its performance was slightly better than Comparative Example 1, but still significantly worse than Example 1. This indicates that traditional sodium silicate solution treatment has limited effectiveness on poorly porous matrices like coal gangue concrete. The hydrated calcium silicate gel generated by the reaction of sodium silicate with cement hydration products is insufficient to completely seal the numerous honeycomb-like pores and microcracks present in coal gangue concrete.
[0071] Comparative Example 3 used a commercially available gel-type styrene-acrylic emulsion instead of the composite emulsion, and its performance was significantly better than Comparative Examples 1 and 2, but still far lower than Example 1. This indicates that although the simple styrene-acrylic emulsion coating has a certain protective effect, it lacks the filling and reinforcing effect of nano-SiO2, resulting in insufficient density and durability of the coating. In Comparative Example 4, no silane coupling hydrophobic agent was used in the concrete, and its surface damage cycle count was approximately 100 cycles. This indicates that without hydrophobic modification of the matrix, even with a surface coating, moisture can still penetrate from coating defects and transport within the matrix. In Comparative Example 5, the coal gangue coarse aggregate was not treated with nano-SiO2, and its surface damage cycle count was approximately 90 cycles. This indicates that the high water absorption rate of the unreinforced coal gangue aggregate itself is a significant cause of freeze-thaw damage. In Comparative Example 6, coal gangue fine aggregate replaced part of the natural fine aggregate, and its surface damage cycle count was approximately 160 cycles, better than Comparative Examples 1-5 but lower than Example 1. This indicates that while using coal gangue fine aggregate can improve the utilization rate of solid waste, it will significantly impair the freeze-thaw resistance of concrete.
[0072] It should be understood that Examples 1-5 use 100mm×100mm×100mm standard cubic specimens as examples of building components for preparation and performance testing. Based on the technical teachings provided by this invention, those skilled in the art can directly use this coal gangue concrete material to manufacture building components of different sizes and shapes, such as concrete blocks, precast drainage ditches, and ditch covers. According to the test results of Examples 1-5, it can be expected that these building components also possess the excellent mechanical properties and freeze-thaw resistance described in this invention.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A coal gangue concrete, characterized in that, The raw materials include the following parts by weight: 4-7 parts ordinary silicate cement, 10-13 parts natural fine aggregate, 5-7 parts coal gangue coarse aggregate, 9-11 parts natural coarse aggregate, 0.04-0.07 parts silane coupling hydrophobic agent, 2-3.5 parts water, and 0.09-0.12 parts polycarboxylate high-performance water-reducing agent.
2. The coal gangue concrete according to claim 1, characterized in that, The coal gangue coarse aggregate is nano-SiO2 reinforced coal gangue coarse aggregate, and its preparation process is as follows: (1) Screen the coarse aggregate of coal gangue with a particle size of 5-20 mm and wash it; (2) After cleaning, put the coarse aggregate of coal gangue into an oven to dry, take it out and cool it to room temperature for later use; (3) Select nano-SiO2 with an average particle size of 15±5nm and prepare it into a solution with a concentration range of 2.7%-3.2%; (4) The dried coal gangue coarse aggregate is completely immersed in the nano silica aqueous solution obtained in step (3) and soaked at 20±2℃ for 24h, stirring once every 6h during the soaking period; (5) After soaking, take out the coarse aggregate of coal gangue, drain the surface moisture and put it into a 60℃ forced-air drying oven to dry to constant weight; (6) After drying, cool to room temperature to obtain the product.
3. The coal gangue concrete according to claim 1, characterized in that, The preparation process of the silane coupling hydrophobic agent is as follows: (1) Weigh the following raw materials according to the following weight proportions: 100 parts mica powder, 5 parts silane coupling agent KH550, and 3 parts polydimethylsiloxane; (2) Add deionized water to the dried mica at a mass ratio of 1:5 and ultrasonically disperse for 30 min; (3) Mix the silane coupling agent KH550 with the ethanol solution at a mass ratio of 1:20 and stir and hydrolyze in a 60℃ water bath for 30 min. The mass ratio of anhydrous ethanol to deionized water in the ethanol solution is 95:
5. Adjust the pH to 4-5 with acetic acid before use. (4) Under stirring conditions, slowly add the hydrolysate obtained in step (3) to the mica slurry obtained in step (2) and mix evenly; (5) Continue stirring the material, add polydimethylsiloxane, stir for 2 hours in a 60°C water bath, filter, and wash the filter cake with anhydrous ethanol. (6) After washing, dry the filter cake to constant weight, grind it and pass it through a 200-mesh sieve to obtain the final product.
4. The coal gangue concrete according to claim 1, characterized in that, The ordinary silicate cement has a strength grade of 42.5, and the ratio of water to ordinary silicate cement is 0.5; the amount of silane coupling hydrophobic agent is 1% of the amount of ordinary silicate cement.
5. The coal gangue concrete according to claim 1, characterized in that, The natural coarse aggregate is crushed stone with a continuous gradation of 5-31.5mm particle size, wherein the ratio of 5-10mm:10-20mm:16-31.5mm is 2:5:3; the natural fine aggregate is medium river sand with a fineness modulus of 2.
6.
6. The coal gangue concrete according to claim 1, characterized in that, The method for preparing the coal gangue concrete includes the following steps: (1) 4-7 parts of ordinary silicate cement, 10-13 parts of natural fine aggregate, 5-7 parts of coal gangue coarse aggregate, 9-11 parts of natural coarse aggregate, 0.04-0.07 parts of silane coupling hydrophobic agent, 2-3.5 parts of water, and 0.09-0.12 parts of polycarboxylate high-performance water-reducing agent; (2) The weighed coal gangue coarse aggregate is pre-wetted until it reaches a saturated surface dry state, then drained of surface moisture and set aside for later use. (3) Add ordinary silicate cement, natural fine aggregate, silane coupling hydrophobic agent, coal gangue coarse aggregate and natural coarse aggregate into a mixer and mix evenly. Then add 70% water and continue mixing evenly. Then add polycarboxylate high-performance water-reducing agent and the remaining water and continue mixing evenly. (4) Pour the mixed slurry into the mold and compact it on the vibrating table. After compaction for 24 hours, remove the mold and cure it in a curing room with a temperature of 20±2℃ and a humidity of ≥95% for 28 days. After curing, coal gangue concrete is obtained.
7. A building component, characterized in that, The component is prepared from the coal gangue concrete according to any one of claims 1-6.
8. A method for improving the freeze-thaw resistance durability of the component as described in claim 7, characterized in that, Includes the following steps: (1) Clean the surface of the component and then let it air dry naturally; (2) Apply the composite emulsion evenly to all exposed surfaces. The amount of coating is 0.25-0.3 kg / m2. After coating, let it stand in a dry environment for 8 hours to allow it to dry completely. Then apply the second coat with the same amount as the first coat. After the second coat is dry, immerse the component in the composite emulsion for about 10 seconds and then remove it. Drain off the excess liquid and cure it in a dry environment for 72 hours to allow it to fully harden.
9. The method for improving the freeze-thaw resistance of a component according to claim 8, characterized in that, The preparation process of the composite emulsion is as follows: (1) Weigh 2 parts of modified nano-SiO2, add 15 parts of deionized water, and ultrasonically disperse for 15 min to prepare a pre-dispersed slurry; (2) Under stirring conditions, the pre-dispersed slurry is slowly added to 100 parts of styrene-acrylic emulsion; (3) Then add 1 part dodecyl alcohol ester, 0.5 part AMP-95 and 0.3 part defoamer to the system in sequence, and stir at 1000 rpm for 15 min to make the components evenly dispersed; (4) Adjust the viscosity of the emulsion to 20-25s using deionized water and let it stand to defoam.
10. The method for improving the freeze-thaw resistance of a component according to claim 9, characterized in that, The preparation process of the modified nano-SiO2 is as follows: (1) Weigh 1 part of nano SiO2 with an average particle size of 30±5nm, add 10 parts of anhydrous ethanol and 5 parts of deionized water, disperse ultrasonically for 30min, and then adjust the pH to 4-5 with dilute hydrochloric acid. (2) Add 0.5 parts of KH560 to the system and continue ultrasonic dispersion for 10 min; (3) Stir the system containing KH560 in a 70°C water bath for 3 hours; (4) After the reaction is complete, centrifuge the product and wash the precipitate; (5) Dry the precipitate under vacuum to constant weight, then grind it.